Abnormalities in Cardiac Structure and Function among Individuals with CKD: The COMBINE Trial. Issue 2 (24th February 2022) - Wang, Ann A.; Cai, Xuan; Srivastava, Anand; Prasad, Pottumarthi V.; Sprague, Stuart M.; Carr, James; Wolf, Myles; Ix, Joachim H.; Block, Geoffrey A.; Chonchol, Michel; Raphael, Kalani L.; Cheung, Alfred K.; et al.
Key Points: Individuals with CKD had lower mitral valve E/A ratio on cardiac magnetic resonance imaging compared with healthy volunteers, suggestive of early diastolic dysfunction. Higher urine albumin-creatinine ratio was significantly associated with lower mitral valve E/A ratio in individuals with CKD with and without baseline cardiovascular disease (CVD). Early changes in diastolic dysfunction in patients with CKD may identify individuals at greatest risk for progression to clinical CVD. Visual Abstract: Abstract : Background: Individuals with CKD have a high burden of cardiovascular disease (CVD). Abnormalities in cardiac structure and function represent subclinical CVD and can be assessed by cardiac magnetic resonance imaging (cMRI). Methods: We investigated differences in cMRI parameters in 140 individuals with CKD stages 3b–4 who participated in the CKD Optimal Management with BInders and NicotinamidE (COMBINE) trial and in 24 age- and sex-matched healthy volunteers. Among COMBINE participants, we examined the associations of eGFR, urine albumin-creatinine ratio (UACR), phosphate, fibroblast growth factor 23 (FGF23), and parathyroid hormone (PTH) with baseline ( N =140) and 12-month change ( N =112) in cMRI parameters. Results: Mean (SD) ages of the COMBINE participants and healthy volunteers were 64.9 (11.9) and 60.4 (7.3) years, respectively. The mean (SD) baseline eGFR values in COMBINE participants were 32.1 (8.0) and 85.9 (16.0) ml/min per 1.73 m 2 in healthy volunteers. The median (interquartile range [IQR]) UACR in COMBINE participants was 154 (20.3–540.0) mg/g. Individuals with CKD had lower mitral valve E/A ratio compared with healthy volunteers (for CKD versus non-CKD, β estimate, −0.13; 95% CI, −0.24 to −0.012). Among COMBINE participants, multivariable linear regression analyses showed that higher UACR was significantly associated with lower mitral valve E/A ratio ( β estimate per 1 unit increase in natural-log UACR, −0.06; 95% CI, −0.09 to −0.03). This finding was preserved among individuals without baseline CVD. UACR was not associated with 12-month change in any cMRI parameter. eGFR, phosphate, FGF23, and PTH were not associated with any cMRI parameter in cross-sectional or change analyses. Conclusions: Individuals with CKD stages 3b–4 have evidence of cMRI abnormalities. Albuminuria was independently associated with diastolic dysfunction, as assessed by mitral valve E/A ratio, in individuals with CKD with and without clinical CVD. Albuminuria was not associated with change in any cMRI parameter.